Efficient Furfuryl Alcohol Synthesis from Furfural over Magnetically Recoverable Catalysts: Does the Catalyst Stabilizing Medium Matter?. Issue 20 (11th July 2017) - Alibegovic, Kenan; Morgan, David Gene; Losovyj, Yaroslav; Pink, Maren; Stein, Barry D.; Kuchkina, Nina V.; Serkova, Elena S.; Salnikova, Kseniya E.; Shifrina, Zinaida B.; Matveeva, Valentina G.; Sulman, Esther M.; Bronstein, Lyudmila M.
Abstract: We report hydrogenation of furfural (FF) to furfuryl alcohol (FA) with novel Pt‐and Pd‐containing magnetite nanoparticles (NPs) stabilized by polyphenylquinoxaline (PPQ) and hyperbranched pyridylphenylene polymer (PPP). FF is one of the major ingredients of biooil produced by biomass pyrolysis, while FA is a source of value‐added chemicals, thus, creating a sustainable path from biomass to important compounds. We demonstrate that catalytic NPs (Pt 0 or Pd 0 ) of approximately 3 nm in diameter form in the polymer shells of magnetite NPs and the catalysts are magnetically recoverable. The search for optimal reaction conditions of the FF hydrogenation revealed that the highest selectivity is obtained at 120 °C and 6 MPa hydrogen pressure in i ‐propanol as solvent. The solvent effect is due to combination of good FF solubility and accessibility of catalytic NPs for the FF adsorption. A comparison of the catalytic activities of the Pd‐containing magnetite NPs stabilized by PPQ and PPP validates the advantages of the open and rigid structure of the hyperbranched PPP vs. linear PPQ. For Pd‐containing magnetite NPs stabilized by PPP, the high selectivity to FA of 99.3% at nearly 100% FF conversion was achieved at a remarkable activity of 871 min −1 and high catalyst stability. Abstract : Catalyst for biooil component hydrogenation: Stabilization of composite Pd‐Fe3 O4 nanoparticles by rigid hyperbranched pyridylphenylene polymer allows for remarkable activity and high selectivity in the furfuryl alcohol synthesis by hydrogenation of the major biooil ingredient, furfural. The magnetic component of the catalyst allows for easy magnetic separation. The catalyst demonstrated high stability in repeated use.